KAJIAN FIQH MUAMALAH TENTANG DAMPAK PENUNDAAN PEMBAYARAN PADA JUAL BELI ISTISHNA - Husnawati, Nurul (MUAMALAH, 2024)
This study deals with how the study of muamalah fiqh on istishna sale and purchase agreements with delayed payments and the impact it has. Delay in payment means deferral of payment of debts that are already collectible to avoid losses. There are two types of buying and selling orders. One of the buying and selling orders is buying and selling istishna. This study aims to find out how in a payment system where the parties already know clearly the price of the item. Meanwhile, in terms of paying off the goods, the buyer often delays the remaining payment.